Análise do sistema construtivo de edifícios de múltiplos pavimentos no Brasil em lajes lisas com cordoalhas engraxadas - Nunes, Harlen (Universidade Federal de São Carlos, 2019)
This work is an unpublished survey on the analysis of the use of a prestressed concrete constructional system with greased corbels in smooth slabs in multi - storey buildings in Brazil, according to the new norm NBR 6118: 2014. It is a critical study with the focus of market exemption on the processes of structural execution and the impact they cause on the cost of the structure. The studies developed so far, in the structural aspect, were made with norms prior to this one, which considers the quality of the structure and the durability beyond the safety conditions that are followed by all the offices of projects of the country. In relation to the study of the constructive processes there are only until then, studies done by companies involved in the procedures and, therefore, possibly without the necessary exemption for a critical judgment. Also, the studies done so far are extremely watertight without raising the project (structural calculation) and the cost of execution (processes and inputs) in detail. There are studies in which only indices of materials (concrete, steel and shape) are established, others that deal with the structural behavior of massive slab, ribbed lattice and ribbed with plastic vats and the conventional structural system (consisting of massive slabs and beams) with that of plain, massive or ribbed slabs, and finally a study that studies comparatively the costs between conventional structural systems and the structural systems of ribbed slabs in reinforced concrete. In this paper we try to understand the differences that exist when one opts for the adoption of the system of flat slabs for multi-storey buildings in detriment to the conventional one. Thus, it is analyzed from the phase of the structural project (what influences the execution and what the main knowledge that must be added to the detailing process), the one of execution, mainly focusing on the question of quantity of service and finally quantifying the cost of a same building executed in the region of Ribeirão Preto considering the conventional systems and the same with prestress slab. As a parameter of analysis to make these simulations, surveys of works in the country and in the region of Ribeirão Preto, interviews between actors involved in the process and bibliographic research were done. It can be concluded that, even in the case of usual buildings (medium size, buildings with usual plant architecture), this type of application can economically and without many technical difficulties be applied in several regions of the country, especially in Ribeirão Preto.
Analysis of the constructive system of multi - storey buildings in Brazil in flat slabs with greased corbels
Keywords: Edificios; Lajes lisas; Cordoalha engraxada; Prédios de múltiplos andares; Processo construtivo; Concreto protendido; Smooth slabs; Greased rope; Multi-story buildings; Construction process; Prestressed concrete; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::PROCESSOS CONSTRUTIVOS; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS::ESTRUTURAS DE CONCRETO